Scanning transmission electron microscopy imaging and analysis - Pennycook, Stephen J.; Nellist, Peter D. Peter David (Springer, 2011)
Scanning transmission electron microscopy has become a mainstream technique for imaging and analysis at atomic resolution and sensitivity, and the editors of this book are widely credited with bringing the field to its present popularity. Scanning Transmission Electron Microscopy: Imaging and Analysis provides a comprehensive explanation of the theory and practice of STEM from introductory to advanced levels, covering the history of the field, the instrument, image formation and scattering theory, as well as practical aspects of imaging and analysis. The authors present examples of the use of combined imaging and spectroscopy for solving materials problems in a variety of fields, including condensed matter physics, materials science, catalysis, and nanoscience. Therefore this is a comprehensive reference for those working in applied fields wishing to use the technique, for graduate students learning microscopy for the first time, and for specialists in other fields of microscopy.